Evaluasi Kontribusi Tenaga Kerja dan Perusahaan terhadap Laba Bersih BUMD: Studi Empiris di Sumatera Barat - Ranti Mustika Putri; Hadigufri Triha; Alima Shofia; Beni Harma; Prima Fithri (SURYA TEKNIKA, 2024)
This study is motivated by the importance of understanding the factors influencing the net profit of Regional Owned Enterprises (BUMD) in West Sumatra Province, particularly in the context of the number of employees and the number of companies. The purpose of this research is to analyze the effect of the number of employees and the number of companies on the net profit of BUMD using multiple linear regression methods. The data used in this study were sourced from the Central Statistics Agency (BPS) for the period from 2013 to 2022. The results of the analysis indicate that the regression model is overall significant with an R2 adjusted value of 0,537, meaning that 53,7% of the variation in net profit can be explained by the number of employees and the number of companies. However, the individual effects of the number of employees and the number of companies on net profit are not statistically significant at the 95% confidence level. The conclusion of this study is that the number of employees and the number of companies collectively influence the net profit of BUMD, although the impact of each variable is not strong enough individually.